Relationship between Atherosclerosis and Cancer: An observational outcome study - Ansgar Adams; Waldemar Bojara; Michel Romanens (Imaging Journal of Clinical and Medical Sciences - Peertechz Publications, 2022)
Background and aims: It was investigated whether there is a relationship between advanced atherosclerosis of the carotid artery and cancer.  Method: The carotid Total Plaque Area (TPA), the maximum plaque thickness, and the cardiovascular risk based on Framingham calculator using body-mass-index were determined in healthy subjects using ultrasound.  We compared the outcome in subjects with advanced atherosclerosis of the carotid artery (type III-IV b finding) with and without statin treatment. The follow-up was collected as part of occupational health check-ups. Result: In 4207 healthy men aged 35-65 years (50±8 years) we found 578 subjects with advanced atherosclerosis of the carotid artery (type III-IV b finding). A follow-up was available for 566 (97.9%) subjects. The average follow-up time was 48 months (range 0 to 139 months). Ten subjects were excluded because of missing data on treatment. A total number of 230 subjects was treated with a statin, 326 received no statin. Within the group of these subjects (54±6 years), 33 men died (15 cancer, 4 strokes, 11 heart attacks, 1 COPD, 1 sepsis, 1 cirrhosis of the liver). In the group with CVD death, two subjects were treated with a statin, 13 were untreated. In the group with cancer death, two subjects were treated with a statin, 13 were untreated. The death rate because of cancer and CVD was 1.7% for the treated subjects and 8.0% for the untreated subjects. In the group with low risk (n= 1890), six men died (2 traffic accidents, 1aneurysm bleeding, 2 cancer, 1 unclear, a follow-up examination has been completed for 43.9% (n= 830) of the subjects, mean follow-up time of 65 months (0-137 months). One man died (Parkinson) within the group with intermediate risk. In this group (n= 482) a follow-up examination has been completed for 55% (n= 265) with a mean follow-up time of 55 months (total range: 0-130 months). In the reference group (no atherosclerosis; n= 1257) follow-up has been completed in 38.3% (n= 482) with a mean follow-up time of 60 (0-145) months and nobody died. In 3203 healthy women aged 35-65 years nobody died of cancer. Conclusion: The development of cancer in men with advanced atherosclerosis of the carotid artery appears to be noticeable. The question of whether there is a causal relationship requires further investigations.